Liquidity Risk Management in Corporate Finance: Strategies for Financial Resilience - Andi Hepy Susanti; Waqiah; Agus Surya Bharmawan; Deti Kurniati; Iradat Rayhan Sofyan (SEULANGA SYSTEM PUBLISHER, 2025)
This study examines the effectiveness of KPI-based performance appraisal systems in improving employee performance within Indonesian non-profit organizations. Focusing on Dompet Dhuafa, Rumah Zakat, and BAZNAS, the research employs a qualitative multiple-case study approach to explore how KPI frameworks are designed, implemented, and perceived by employees and management. Data were collected through in-depth interviews, participatory observation, and document analysis, and analyzed thematically using Braun and Clarke’s six-step framework.The findings reveal that KPI systems play a crucial role in aligning individual performance with organizational missions, enhancing accountability, and motivating employees. They were found to improve task performance, contextual contributions such as teamwork and initiative, and adaptive performance, particularly in the use of digital tools and responsiveness to community needs. Employees also reported increased job satisfaction when KPIs were applied transparently and supported by constructive feedback mechanisms Nevertheless, the study identifies significant challenges in the implementation of KPI systems. These include rigid indicators that overlook intangible contributions, limited digital infrastructure, cultural barriers, and additional administrative burdens for employees. Despite these obstacles, strategies such as customizing KPI indicators, promoting participatory approaches, providing continuous feedback, leveraging external partnerships, and investing in capacity-building were found to enhance the effectiveness of KPI systems In conclusion, KPI-based appraisal systems have strengthened performance management in Dompet Dhuafa, Rumah Zakat, and BAZNAS. Their long-term success depends on balancing accountability with flexibility and ensuring that systems are responsive to the unique missions of non-profit organizations.